Barx2 and Pax7 Regulate Axin2 Expression in Myoblasts by Interaction with β‐Catenin and Chromatin Remodelling. (6th June 2016) - Hulin, Julie‐Ann; Nguyen, Thi Diem Tran; Cui, Shuang; Marri, Shashikanth; Yu, Ruth T.; Downes, Michael; Evans, Ronald M.; Makarenkova, Helen; Meech, Robyn
Abstract: Satellite cells are the resident stem cells of skeletal muscle; quiescent in adults until activated by injury to generate proliferating myoblasts. The canonical Wnt signalling pathway, mediated by T‐cell factor/lymphoid enhancer factor (TCF/LEF) and β‐catenin effector proteins, controls myoblast differentiation in vitro, and recent work suggests that timely termination of the Wnt/β‐catenin signal is important for normal adult myogenesis. We recently identified the Barx2 and Pax7 homeobox proteins as novel components of the Wnt effector complex. Here, we examine molecular and epigenetic mechanisms by which Barx2 and Pax7 regulate the canonical Wnt target gene Axin2, which mediates critical feedback to terminate the transcriptional response to Wnt signals. Barx2 is recruited to the Axin2 gene via TCF/LEF binding sites, recruits β‐catenin and the coactivator GRIP‐1, and induces local H3K‐acetylation. Barx2 also promotes nuclear localization of β‐catenin. Conversely, Pax7 represses Axin2 promoter/intron activity and inhibits Barx2‐mediated H3K‐acetylation via the corepressor HDAC1. Wnt3a not only induces Barx2 mRNA, but also stabilises Barx2 protein in myoblasts; conversely, Wnt3a potently inhibits Pax7 protein expression. As Barx2 promotes myogenic differentiation and Pax7 suppresses it, this novel posttranscriptional regulation of Barx2 and Pax7 by Wnt3a may be involved in the specification of differentiation‐competent and ‐incompetent myoblast populations. Finally, we propose a model for dual function of Barx2 downstream of Wnt signals: activation of myogenic target genes in association with canonical myogenic regulatory factors, and regulation of the negative feedback loop that limits the response of myoblasts to Wnt signals via direct interaction of Barx2 with the TCF/β‐catenin complex. Stem Cells 2016;34:2169–2182